ANÁLISE ULTRAESTRUTURAL E NANOMECÂNICA DO VÍRUS SARS-CoV-2 - LIMA, Ruana Cardoso (2022)
The ongoing outbreak of the severe acute respiratory syndrome coronavirus2 (SARSCoV2) started in later 2019 and spread across the world, infecting millions of people with over 5 million deaths worldwide. To fight back the virus is necessary to understand how its main structures function, especially those responsible for the virus infectivity pathogenicity. Understanding from the physical point of view the structure and properties of SARSCoV2 is extremely impor tant to find vulnerable points that can elucidate the mechanisms of drug targeting, for example. Determining the ultrastructure and nanomechanical properties of SARSCoV2 can clasifiy its mechanical properties and shed light on new treatment routes. This study has Atomic Force Microscopy as the main tool for the investigation of the ultrastructure and nanomechanical pro perties of the SARSCoV2 inactivated virion. Here, using the most advanced Atomic Force Microscopy techniques, SARSCoV2 viral particles were analyzed, with an especial focus on their ultrastructure, adsorption conformation and nanomechanical behavior. The results uncove red aspects of the organization and the spatial distribution of the proteins on the surface of the viral particles. It was also shown the compliant behavior of the membrane and ability to reco ver from mechanical injuries. At least three layers composing the membrane and their thickness were measured. This study provides new insight into the ultrastructure of SARSCoV2 particles at the nanoscale offering new prospects that could be employed for mapping viral surface.